SECONDARY STUDENTS’ PROFILE AND SCHOLASTIC PERFORMANCE DURING COVID-19: THE CASE OF A LABORATORY SCHOOL IN THE PHILIPPINES - Cabuquin, Jomar C.; Brun, Richard S.; Mercado, Henry Alwayne R. (International Journal of Education, 2023)
Students' performance in the classroom can be viewed as vital since an aptitude for learning and intelligence can pave the way for their future success in both the workplace and the economy. This study examined the secondary students' profile and scholastic performance during the COVID-19 pandemic at a laboratory school in Eastern Visayas, Philippines. It utilized the quantitative approach to ascertain the variation among the specified study variables involving 620 secondary students from different grade levels. Secondary data on students' profile variables and scholastic performance were obtained from the school's Learner Information System (LIS). The T-test for two independent samples was likewise utilized to examine the significant difference in the performance of male and female students according to grade levels. Based on the results, majority of the students used mobile data and broadband as means to access the internet. Moreover, the online and blended learning were the student's preferred learning modalities. However, the inadequacy of gadgets available, insufficient load, intermittent mobile or internet access, existing health conditions, difficulty in self-regulated learning, conflict with other activities, and high electrical consumption and distractions were among the challenges students faced during the pandemic. Meanwhile, the students displayed very satisfactory to outstanding scholastic performance amidst COVID-19. Likewise, the study found no significant performance difference between male and female students in grades 8 and 12, in contrast to other grade levels. Therefore, creating flexible and responsive teaching practices in the current and post-pandemic educational environment and the enhancement of internet connectivity is recommended.